The Effects of Financial Literacy on entrepreneurial Success amongst University students. - Arineitwe Simon (Uganda Christian University, 2024)
ABSTRACT Financial literacy has been documented as a vital factor in poverty lessening and enhancing employability rates. However, there is a scarcity of empirical evidence on the specific mechanisms through which financial literacy effects entrepreneurial Success, particularly among university students. Despite the recognized importance of financial literacy in poverty reduction and enhanced employability rates there is limited empirical evidence on the underlying mechanisms of change in the context of entrepreneurial Success. To address this gap, the study explores the effects of financial literacy entrepreneurial Success, while also examining potential variations in this relationship based on gender and socioeconomic status. The study found that participants had average financial literacy, with room for growth in understanding specific financial products and services. Although there was a significant tendency towards entrepreneurship, practical involvement and training in entrepreneurial activity differed. The study discovered a positive relationship between entrepreneurial success amongst university students, emphasizing the importance of financial knowledge and decision-making abilities, and awareness of financial products and services in generating entrepreneurial aspirations. Gender and socioeconomic status were investigated as potential moderating factors, and while some connections were detected, they were not consistently strong or statistically significant across all variables. This study emphasizes the significance of focused interventions to increase financial literacy and practical engagement, notably through integrated curriculum creation, experiential learning, mentorship, resource centers, public awareness campaigns, and longitudinal studies. Finally, this study adds to our understanding of financial literacy and entrepreneurial success amongst university students. Academic institutions may equip students to manage the difficulties of entrepreneurship with confidence by encouraging financial literacy and an entrepreneurial mindset, ultimately contributing to economic growth and development. Future study ideas include longitudinal investigation